The Effect of H-Factor on Kappa Number and Viscosity in Continuous Digester - Putri, Rizka Wulandari; Rahmatullah, Rahmatullah; Siagian, Faisal (CHEESA: Chemical Engineering Research Articles, 2023)
One of the most important steps in pulping is the cooking process, which serves to separate the cellulose and hemicellulose from lignin and other by-products. During the cooking process in the digester, various factors must be considered to create high-quality pulp. Among these factors, the H-Factor plays a significant role due to its impact on the kappa number and viscosity in the pulping process. A high H-Factor can also damage the strength of the pulp. Therefore, this research aims to investigate the effect of the H-Factor and active alkali on pulp yield and quality. The active alkali used was in line with the desired production objectives, as insufficient levels of active alkali can lead to a low yield of pulp. Meanwhile, pulp quality standards in the Pulp and Paper Industry included kappa number of 12-18 in the digester process, an approximate viscosity of 23 mPa.s, and the selection of H-Factor based on the desired production target.